2012
DOI: 10.7314/apjcp.2012.13.8.3997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes and MicroRNAs Involved in Ovarian Carcinogenesis

Abstract: MicroRNAs (miRNAs) play roles in the clinic, both as diagnostic and therapeutic tools. The identification of relevant microRNAs is critically required for ovarian cancer because of the prevalence of late diagnosis and poor treatment options currently. To identify miRNAs involved in the development or progression of ovarian cancer, we analyzed gene expression profiles downloaded from Gene Expression Omnibus. Comparison of expression patterns between carcinomas and the corresponding normal ovarian tissues enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Ting Guan' lab obtained a total of 18 key miRNAs which may play important regulatory roles in ovarian cancer (Wan et al, 2012). MicroRNA-101 Inhibits Cell Proliferation, Invasion, and Promotes Apoptosis by Regulating Cyclooxygenase-2 in Hela Cervical Carcinoma Cells (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ting Guan' lab obtained a total of 18 key miRNAs which may play important regulatory roles in ovarian cancer (Wan et al, 2012). MicroRNA-101 Inhibits Cell Proliferation, Invasion, and Promotes Apoptosis by Regulating Cyclooxygenase-2 in Hela Cervical Carcinoma Cells (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wan et al (2012) recently reported that most of the up-regulated genes were related to cell cycling. The cell cycle dissection is regulated by numerous molecular pathways and specific access points (Figure 2).…”
Section: Mirnas In Cell Cycle Regulationmentioning
confidence: 99%
“…Functional studies performed in cancer ce ll lines or animal models of various cancers suggest that, miRNAs can function as tumor suppressors, oncogenes, and regulate cancer pathways (Farazi et al, 2011). Aberrant expression of specific miRNAs has been reported in many tumor types 1 such as CRC, breast cancer, cervical cancer, non-small cell lung cancer, ovarian cancer and bladder cancer as well as being associated with patients' survival data, metastasis, and other clinicopathological factors (Toyama et al, 2012;Wan et al, 2012;Shen et al, 2013;Wang et al, 2013;Xiao et al, 2013;Liu et al, 2014;Xu et al, 2014). A previous study showed that miR-32 expression was upregulated in CRC tissues, and high expression was significantly correlated with the tumor stage, distal metastases and poor prognoses (Wu et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%